Impact mechanism of green supply chain management on enterprise innovation performance, mediating role of strategic flexibility and moderating effect of environmental scanning - Wang, Wenjuan (Edelweiss Applied Science and Technology, 2025)
In view of the problem that traditional green supply chain management (GSCM) cannot stably improve enterprise innovation performance (IP) due to the lack of systematic mechanism analysis, this paper proposes a comprehensive analysis method based on the structural equation model (SEM), taking strategic flexibility (SF) as the mediating variable and environmental scanning (ES) as the moderating variable to reveal its causes and solutions. This study first quantifies the level of green practice by designing measurement indicators of GSCM and collecting enterprise data. Then, the scale of SF is developed, and data is collected to test its role as a mediating variable. Next, the ES scale is designed, and its moderating effect is verified through interaction analysis. Finally, the objective data of enterprise IP is taken as the dependent variable, and the SEM is constructed to analyze the effects of each variable. The experimental results show that based on the method of this paper, under high environmental scanning conditions, GSCM can achieve an enterprise innovation performance of 5.5 (maximum 6.0) through strategic flexibility, which provides a theoretical basis and practical guidance for optimizing GSCM.